From Theory to Practice: Implementing Ta'limul Muta'allim in Modern Education Systems - Asbari, Danish Akbar Firdausy; Asbari, Raihan Arsyad Firdausy; Nurhayati, Wakhida; Asbari, Masduki (International Journal of Social and Management Studies, 2024)
This study examines the impact of Burhanuddin Az-Zarnuji's classical educational text, "Ta'limul Muta'allim," on student performance and ethical behavior within modern educational contexts. Utilizing a qualitative descriptive methodology, this research explores how the integration of Az-Zarnuji's principles influences academic achievement, student motivation, and moral conduct. Data were collected through interviews, surveys, and observations involving students and educators who have implemented the teachings of "Ta'limul Muta'allim" in their educational practices. The findings indicate significant improvements in various aspects of students' educational experiences. Academically, students demonstrated higher test scores and a deeper understanding of their subjects, attributed to the structured and disciplined study habits promoted by Az-Zarnuji. In terms of motivation, students reported increased enthusiasm and commitment to their studies, driven by the intrinsic value of knowledge emphasized in "Ta'limul Muta'allim." Moreover, there was a notable enhancement in students' ethical behavior, with a decline in instances of academic dishonesty and an increase in mutual respect among peers and towards teachers. Educators observed that the holistic approach of "Ta'limul Muta'allim" not only improved academic performance but also fostered a more respectful and ethically sound learning environment. The study underscores the relevance of integrating ethical and moral education into contemporary curricula, suggesting that the principles of "Ta'limul Muta'allim" can effectively address current educational challenges by promoting both intellectual and character development. This research contributes to the growing body of literature on the applicability of classical educational theories in modern settings and offers practical insights for educators and policymakers aiming to enhance the holistic development of students. Further research is recommended to explore the long-term impacts and broader applicability of Az-Zarnuji's teachings across different educational contexts.